Increased corticosterone in peripubertal rats leads to long-lasting alterations in social exploration and aggression - Veenit, Vandana; Cordero, María I.; Tzanoulinou, Stamatina; Sandi, Carmen (Frontiers in Behavioral Neuroscience, 2013)
Stress during childhood and adolescence enhances the risk of psychopathology later in life. We have previously shown that subjecting male rats to stress during the peripubertal period induces long-lasting effects on emotion and social behaviors. As corticosterone is increased by stress and known to exert important programming effects, we reasoned that increasing corticosterone might mimic the effects of peripubertal stress. To this end, we injected corticosterone (5 mg/kg) on 7 scattered days during the peripuberty period (P28-P30, P34, P36, P40 and P42), following the same experimental schedule as for stress administration in our peripubertal paradigm. We measured play behavior in the homecage and, at adulthood, the corticosterone response to novelty and behavioral responses in tests for anxiety- and depression-like behaviors, aggression and social exploration. As compared to vehicle, corticosterone-treated animals exhibit more aggressive play behavior during adolescence, increased aggressive behavior in a resident-intruder test while reduced juvenile exploration and corticosterone reactivity at adulthood. Whereas the corticosterone treatment mimicked alterations induced by the peripuberty stress protocol in the social domain, it did not reproduce previously observed effects of peripuberty stress on increasing anxiety-like and depression-like behaviors, respectively evaluated in the elevated plus maze and the forced swim tests. Our findings indicate that increasing corticosterone levels during peripuberty might be instrumental to program alterations in the social domain observed following stress, whereas other factors might need to be recruited for the programming of long-term changes in emotionality. Our study opens the possibility that individual differences on the degree of glucocorticoid activation during peripuberty might be central to defining differences in vulnerability to develop psychopathological disorders coursing with alterations in the social realm.